Conceptualizing and testing a new tripartite measure of coach interpersonal behaviors. (September 2019) - Bhavsar, Nikita; Ntoumanis, Nikos; Quested, Eleanor; Gucciardi, Daniel F.; Thøgersen-Ntoumani, Cecilie; Ryan, Richard M.; Reeve, Johnmarshall; Sarrazin, Philippe; Bartholomew, Kimberley J.
Abstract: Objectives: Various self-report measures based on Self-Determination Theory (Deci & Ryan, 1985; Ryan & Deci, 2017) have been developed to assess athletes' perceptions of their coaches' need supportive and thwarting behaviors. We propose that it is also conceptually important to distinguish between coaching behaviors that thwart and those that are indifferent to athletes' psychological needs. This distinction is useful, as we contend that athletes' degree of need frustration, and concomitant negative outcomes, are likely to be more pronounced in a coaching environment that actively thwarts (vs. is indifferent to) athletes' needs. In this three-study paper, we outline the conceptual rationale for, the development of, and initial validity evidence for a tripartite (need supportive, thwarting, and indifferent) measure of interpersonal behaviors of coaches (TMIB-C). Method: In Study 1, we developed 54 candidate items and gathered evidence for their face and content validity with athletes and an expert panel. Competing factor models were tested in Study 2 to determine the best representation of the measure's factor structure. In Study 3, we tested the replication of such models and the nomological network surrounding the identified factors. Results: In Study 2, a 22-item, three-factor structure (supportive, thwarting, and indifferent behaviors) using exploratory structural equation modeling, demonstrated acceptable fit, good standardized factor loadings, factor correlations in the expected directions, and acceptable estimates of internal consistency. This model was replicated in Study 3. Tests of nomological networks showed that as expected, need indifference was a weaker predictor of autonomy and competence need frustration as compared to need thwarting, and the only significant predictor of irrelevant thoughts. Unexpectedly however, need indifference, when compared to need thwarting, was as good a predictor of exhaustion and a better predictor of relatedness frustration. Conclusions: Evidence supports the TMIB-C as a parsimonious and promising measure of athletes' perceptions of coach interpersonal behaviors. Our tripartite conceptualization and measure should be further tested in terms of its predictive utility in order to advance conceptual understanding and intervention efforts targeting interpersonal behaviors in sport, and potentially other life domains. Highlights: Interpersonal behaviors were classified as need supportive, thwarting, and indifferent. A new tripartite measure of coach interpersonal behaviours was developed. A 22-item three-factor ESEM solution provided the best fit to the data. Need indifference was operationally distinguished from need support, and need thwarting. Distinct predictive value of the three interpersonal behaviours is discussed.